The effect of different honey concentrations on the ultrastructure profile of spermatozoa in Dewa Mahseer (Neolissochilus soro) - ABINAWANTO ABINAWANTO; SUCI LESTARI; ANOM BOWOLAKSONO; ASTARI DWIRANTI; RETNO LESTARI; RUDHY GUSTIANO; ANANG HARI KRISTANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Abinawanto A, Lestari S, Bowolaksono A, Dwiranti A, Lestari R, Gustiano R, Kristanto AH. 2023. Title The effect of different honey concentrations on the ultrastructure profile of spermatozoa in Dewa Mahseer (Neolissochilus soro). Biodiversitas 24: 1025-1031. Dewa Mahseer (Neolissochilus soro) is one of Indonesia's endemic freshwater fish at risk of population decline due to water pollution and asynchronous maturation of gonads. One of the efforts to conserve this species is preserving their spermatozoa using honey as a protector at certain temperatures. Therefore, this study aims to evaluate the effect of multiflora honey concentrations on ultrastructure spermatozoa profile of Dewa Mahseer. The temperature was maintained at 4°C and stored for 48 hours, followed by the cement dilution (1:10) in a stock solution containing fish ringer and honey. Transmission electron microscopy (TEM) examined the spermatozoa profiles at a magnification of ×1,500. Furthermore, ANOVA one-way analysis of variance was conducted to test the effect of head length, width, and area of spermatozoa on honey. The results showed a statistically significant difference in head width (F=13.929, p=0.001). Also, there is a difference in area between honey spermatozoa, fresh spermatozoa, and without honey at a cold of 4°C. The fresh spermatozoa stored at cold temperatures without honey observed considerable membrane damage. The novel aspect is an investigation of the effect of honey as a natural protector in the storage of Neolissochilus spermatozoa at 4°C for 48 hours. This study can be applied as a guide for the 48 hours of spermatozoa in a cold temperature in fish farming.